INTERPERSONAL RELATIONSHIP BETWEEN USERS AND HEALTH PROFESSIONALS IN PSYCHOSOCIAL CARE - Maria Cicera dos Santos de Albuquerque; Mércia Zeviani Brêda; Willams Henrique da Costa Maynart; Darlan dos Santos Damásio Silva; Elaine Cristina de Medeiros Moura (Universidade Federal do Paraná, 2016)
The objective in this study was to identify how the interpersonal relationship is established between users and health professionals from the perspective of the users of a Psychosocial Care Center type II in Maceió, Alagoas. Qualitative and exploratory research, undertaken between 2010 and 2012. Data were collected from eight users. Triangulation was used through in-depth semi-structured interviews, non-participant observation and a field diary. Minayo's qualitative analysis was applied to the data. Three categories emerged: 1. Sensitive looking; 2. Establishing the bond; 3. Skills of professionals working at the mental health service. The following results were identified: relationship is fundamental for psychosocial care; it is important for the professional to adopt a humane look towards the user; the bond mitigates suffering; listening and attention skills are decisive to establish trust. The need is observed to discuss the theme interpersonal relationship with the professionals from the service, with a view to enabling them to create and strengthen the bond in comprehensive mental health care